2008
DOI: 10.1128/aem.02212-07
|View full text |Cite|
|
Sign up to set email alerts
|

Sheathless Mutant of Cyanobacterium Gloeothece sp. Strain PCC 6909 with Increased Capacity To Remove Copper Ions from Aqueous Solutions

Abstract: The cyanobacterium Gloeothece sp. strain PCC 6909 and its sheathless mutant were tested for their abilities to remove copper ions from aqueous solutions, with the aim of defining the role of the various outermost polysaccharidic investments in the removal of the metal ions. Microscopy studies and chemical analyses revealed that, although the mutant does not possess a sheath, it releases large amounts of polysaccharidic material (released exocellular polysaccharides [RPS]) into the culture medium. The RPS of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 39 publications
3
30
0
1
Order By: Relevance
“…Gloeothece wt and mt cultures grown at 30 uC and under continuous illumination provided by cool white fluorescent tubes [100 mmol photons (PAR) m 22 s 21 ] were placed in dialysis tubes (12-14 kDa of molecular weight cut-off; Medicell International) and dialysed before and after a pre-treatment with 0.1 M HCl as described previously (Micheletti et al, 2008b). Subsequently, 30 ml confined dialysed cultures were incubated in 80 ml aqueous solutions containing 10 mg l 21 Cu 2+ or Pb 2+ (mono-metal systems) or 10 mg l 21 each metal (bimetal system) for at least 24 h. The pH of the system (biosorbent+ metal solution) was adjusted to 4.5-5.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gloeothece wt and mt cultures grown at 30 uC and under continuous illumination provided by cool white fluorescent tubes [100 mmol photons (PAR) m 22 s 21 ] were placed in dialysis tubes (12-14 kDa of molecular weight cut-off; Medicell International) and dialysed before and after a pre-treatment with 0.1 M HCl as described previously (Micheletti et al, 2008b). Subsequently, 30 ml confined dialysed cultures were incubated in 80 ml aqueous solutions containing 10 mg l 21 Cu 2+ or Pb 2+ (mono-metal systems) or 10 mg l 21 each metal (bimetal system) for at least 24 h. The pH of the system (biosorbent+ metal solution) was adjusted to 4.5-5.5.…”
Section: Methodsmentioning
confidence: 99%
“…PCC 6909 and its sheathless mutant Gloeothece sp. CCY 9612 (obtained by random chemical mutagenesis and still largely uncharacterized) to remove copper ions from aqueous solutions, and demonstrated that specific binding sites for Cu 2+ were present in the sheath of the wild-type and in the RPS of both the wildtype and the mutant, with the RPS of the mutant being the more effective polymer (Micheletti et al, 2008b). The aim of this work was to evaluate the effects of different concentrations of Cu 2+ and/or Pb 2+ in the growth/survival of the two phenotypes, as well as changes in their ultrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it was not until relatively recently that this large and diverse production received significant consideration resulting in their use as industrial gums, bioflocculants, emulsifiers, viscosifiers, medicines, soil conditioners, and biosorbants (Li et al 2001). The sugar compositions of CPSs can be markedly different to those of the RPSs suggesting different biosynthesis mechanisms, that are, in turn, dependent on environmental conditions (Li et al 2001;Micheletti et al 2008). Responses of cyanobacteria to different experimental conditions, however, seem to be species-and/or strain-dependent making more difficult the optimization of exopolysaccharide production (Pereira et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…-в пищевых и фармакологических технологиях в качестве альтер-нативы пектину высших растений (Fang et al, 2008); -в фармацевтической индустрии в качестве антивирусных, анти-канцерогенных и иммуностимулирующих агентов (Jeong et al, 2012); -в качестве эффективных хелаторов тяжелых металлов (Paperi et al, 2006;Micheletti et al, 2008).…”
Section: рис 4 динамика роста микроводорослейunclassified